2018
DOI: 10.1186/s40621-018-0175-6
|View full text |Cite
|
Sign up to set email alerts
|

The burden of hospitalized sports-related injuries in children: an Australian population-based study, 2005–2013

Abstract: BackgroundThere is concern about recent increase and severity of sports-related injuries in children. Despite the benefits of sports participation, injuries may carry long-term health consequences. We aimed to evaluate the prevalence, characteristics and types of hospitalized sports-related injuries in children.MethodsPopulation-based study of all acute sports-related injuries requiring hospitalization in children 5 to 15 years of age in New South Wales (NSW), Australia, 2005–2013. Health information was obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 41 publications
(46 reference statements)
1
15
0
1
Order By: Relevance
“…Our study showed that the school age group most commonly sustained fall injuries outside during sport and play activities, and this is comparable to findings in other settings (Ali et al 2019;Wadhwaniya et al 2017;Unni et al 2012;Gupta et al 2016;Schneuer et al 2018). Therefore, fall injury prevention in school children should focus on safe sports and play, by promoting the use of helmets, protective padding, and safety nets.…”
Section: Discussionsupporting
confidence: 86%
“…Our study showed that the school age group most commonly sustained fall injuries outside during sport and play activities, and this is comparable to findings in other settings (Ali et al 2019;Wadhwaniya et al 2017;Unni et al 2012;Gupta et al 2016;Schneuer et al 2018). Therefore, fall injury prevention in school children should focus on safe sports and play, by promoting the use of helmets, protective padding, and safety nets.…”
Section: Discussionsupporting
confidence: 86%
“…Sports-related injuries are commonly reported among older age group children, more speci cally, males 7 years of age and older. Studies from Canada, the United States, and Australia yielded similar patterns of sports injuries among school-aged children 6-10 years of age [34,41,42]. These types of injuries call for the establishment of safe play areas and outdoor environments with playgrounds meeting international standards for safety to reduce preventable injuries [43].…”
Section: Discussionmentioning
confidence: 95%
“…Child injury, in particular, is a substantial public health problem that claims more children's lives than any major diseases combined [1]. Play-and sport-related injury is one of the leading causes of child injury worldwide [2][3][4]. Most of these injuries occur at school premises where children spend a considerable number of days per year.…”
Section: Introductionmentioning
confidence: 99%